Pemberdayaan Pelaku UMKM di Kawasan Wisata Bandar Grissee Melalui Cokro Ekraf Festival - Berlianda Khisbatul Ifadah; Singgih Manggalou (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The Office of Tourism and Creative Economy, Culture, Youth, and Sports of Gresik Regency has initiated a program to empower Micro, Small, and Medium Enterprises (MSMEs) through the integration of the tourism and creative economy sectors in the Bandar Grissee tourism area, which is realized through the launch of the Cokro Ekraf Festival program. This study aims to examine how the empowerment of MSMEs is implemented through the program. This research employs a descriptive qualitative method with a case study approach. Data collection techniques include observation, interviews, and documentation. The data analysis process followed four systematic stage: data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that at the planning stage, The Office of Tourism and Creative Economy, Culture, Youth, and Sports of Gresik successfully identified the potential of the tourism area and MSME actors, analyzed their needs, and designed programs accordingly. At the implementation stage, the program was carried out routinely and in a well-coordinated manner. In terms of outcomes, the program positively impacted MSMEs by increasing their turnover and expanding market access. However, some technical obstacles were identified, such as time discipline and limited promotional efforts. Program evaluations were conducted both internally and annually by involving stakeholders and MSME actors. In conclusion, the Cokro Ekraf Festival has demonstrated a positive contribution to the empowerment of MSMEs in the Bandar Grissee tourism area.